Co Liner Impact on Microstructure of Cu Interconnects. (1st January 2015) - Zhang, Xunyuan; Cao, Linjun; Ryan, Vivian; Ho, Paul S.; Taylor, Bill; Witt, Christian; Labelle, Cathy
Abstract : The microstructure of Cu interconnects fabricated with Ta and Co liner materials had been examined by transmission electron microscopy and correlated to the electrical characteristics. Cu lines of 40 nm width were fabricated on 300 mm Si wafers by conventional CMOS backend processing. Electrical measurements performed immediately after fabrication of these Cu lines showed similar electrical resistance for Co and Ta liners. However, a 2.5-hour anneal at 375°C led to 5% more resistance reduction for Cu lines with the Ta liner than with the Co liner. Microstructure analyses showed that Cu lines with the Ta liner had 24% coherent Σ3 grain boundaries while lines with the Co liner yielded only 6% of coherent grain boundaries. In addition, Cu with Ta liner had a stronger 〈111〉 texture along the line width direction. However, the overall grain size distribution was similar between Ta and Co liners. These results suggest Co liner has some impact on Cu microstructures, which may be a root cause for the relatively higher line resistance.